Analysis of the state of the gas market in the context of the aggravation of the Ukrainian crisis - E. A. Rechkina; A. M. Terekhov (Вестник университета)
The article characterizes the global natural gas market, identifies the main regions of gas consumption and production, pricing features, the impact of inter-fuel competition, as well as sensitivity to the impact of political risks. The purpose of the article is to determine the causal relationships between the factors influencing the dynamics of the global gas market during periods of escalation of conflicts on a regional scale. Based on the results of the study, a development forecast of the natural gas market was made founded on the constructed economic and mathematical model, which showed an increase in prices in the next few months. The main requirement for the model is its stability to the dynamics of macroeconomic indicators, exchange rates, as well as financial instruments that affect energy and environmental security in the world. Special attention is paid to the study of approaches to assessing the indicators of the gas market.